2014
DOI: 10.2478/opli-2014-0002
|View full text |Cite
|
Sign up to set email alerts
|

Nasal place assimilation and the perceptibility of place contrasts

Abstract: Typological studies of place assimilation show that nasal consonants are more likely to assimilate in place than oral stops

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…Kawahara and Garvey (2014) provide evidence from an identification in noise paradigm that English place contrasts for nasals and stops are more confusable in pre-stop than word-final position. Comparing the two experiments reported in Kochetov and So (2007), one with final stops at the ends of isolated words and the other with a following consonant-initial context, suggests the same conclusion.…”
Section: Contrast and Positional Neutralizationmentioning
confidence: 96%
See 1 more Smart Citation
“…Kawahara and Garvey (2014) provide evidence from an identification in noise paradigm that English place contrasts for nasals and stops are more confusable in pre-stop than word-final position. Comparing the two experiments reported in Kochetov and So (2007), one with final stops at the ends of isolated words and the other with a following consonant-initial context, suggests the same conclusion.…”
Section: Contrast and Positional Neutralizationmentioning
confidence: 96%
“…Kawahara and Garvey (2014) test this directly for English speakers with both similarity judgments and identification in noise: nasal place is less perceptible than oral-stop place in both domain-final and preconsonantal position. Similarity measures derived from raw confusion matrices in English (Woods et al, 2010) and Dutch (Pols, 1983) show that nasals differing in place are more confusable than stops differing in place in both initial prevocalic and domain-final position.…”
Section: Contrast and Positional Neutralizationmentioning
confidence: 96%
“…Typological patterns are consistent with this prediction: targets of assimilation commonly occur in typologically weak positions (word-final/coda/preconsonantal) while triggers tend to occur in strong positions (word-initial/onset/prevocalic) (see e.g. Ohala & Ohala 1993;Beddor & Evans-Romaine 1995;Jun 1995Jun , 2011Boersma 1998;Kawahara & Garvey 2014).…”
Section: Assimilationmentioning
confidence: 67%
“…However, perceptual evidence regarding this asymmetry has been inconsistent, with some authors finding coronal salience to be high, while others found it low (Mohr & Wang 1968, Pols 1983, Winters 2001, 2003, Hura et al 1992, Wang & Fillmore 1961, Singh & Black 1966, Kochetov & So 2007, Kochetov & Pouplier 2008. Such inconsistent results are partly attributed to various experimental conditions, including the number of talkers in the stimuli (one vs. multiple talkers), the structure of stimuli (isolated syllable vs. clusters), the treatment of the release burst (absence vs. presence of the burst), and listening conditions (see Winters 2001, Kawahara & Garvey 2014.…”
Section: Chapter Introductionmentioning
confidence: 81%